Erosive Pustular Dermatosis of the Scalp Induced by Imiquimod - Maria Teresa Corradin; Marina Forcione; Erika Giulioni; Renzo Fiorentino; Anna Ferrazzi; Mauro Alaibac (Hindawi Limited, 2012)
Erosive pustular dermatosis of the scalp (EPDS) is a rare condition characterized by sterile pustules, erosions, and crusted lesions on the scalp of elderly patients. This inflammatory disorder has an unknown origin and it could develop into areas of alopecia that tend to be atrophic. An 84-year-old Caucasian man presented with a several months history of painful erythematous erosions and crusts on his scalp. The lesions appeared after treatment with imiquimod cream for actinic keratoses. Previous therapies included topical antibiotics and topical steroids. Physical examination revealed the presence of extensive erosions and crusts on the scalp, with minute pustules on the sides. The clinical features and the medical history led us to the diagnosis of EPDS. Treatment with systemic steroid was administered with improvement observed after ten days. The clinical manifestations of EPDS completely resolved after 2 months, without clinical relapses.